A COMPREHENSIVE LITERATURE REVIEW ON TIME VALUE OF MONEY AND ECONOMIC VALUE OF TIME FOR FINANCIAL DECISION-MAKING - Lahuri, Setiawan bin; Wardani, Baiq Alfina Rahma; Zuhroh, Ainun Amalia (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2025)
This study aims to analyze the concept of economic value of time as an answer to the distractions concept of time value of money by conventional views. The significance of comprehending the distinction between the temporal value of money and the economic value of time for the Muslim community to prevent entrapment in usurious transactions. Money in the conventional impacted to the continuous passage of time which requires an increase in face value to increase. This concept is referred to as the time value of money. As a result, this concept is related to the concept of discounting which in reality indirectly associates itself with the term "interest" that forbident for each muslim. Library analysis method used for this research through the data from literacy from book and previous article journal. According to the research's findings, the traditional understanding of money as having a time value (the "time value of money") holds that money today is worth more than money tomorrow and that the advantages of acquiring money now will outweigh those of acquiring benefits later. That's why this concept is not the best way out if applied in the economic process. Because this concept can give rise to a habit of people who will only save their money if the interest rate on the bank is at a high level, which is close to the act expected in Islam, namely usury. Therefore, Islam in this case holds that what is actually not money that has time value but time that has economic value of time.